TANTANGAN TENAGA KERJA DI PROVINSI BALI SETELAH PANDEMI COVID-19 - I Made Putra Yasa; I Putu Hedi Sasrawan; I Gusti Agung Ayu Apsari Anandari; Made Sinthya Aryasthini Mahaendrayasa (Nusantara Hasana Journal, 2024)
Indonesia's province of Bali was heavily impacted by the COVID-19 pandemic, with its economy experiencing a decline of 9.34% in 2020. Even in 2022, Bali's economy has not fully recovered, while other provinces have already recorded economic growth in 2021. Post-pandemic numbers unemployment in the province of Bali increased from around 1 percent before 2020 to above 5 percent as of August 2022. Unemployment conditions have not improved significantly even though the economy has grown to near normal by 4.84 percent in 2022. This is inseparable from the sector of providing accommodation and food and drink which is one of the largest contributions to the Gross Regional Domestic Product (GRDP) of Bali Province. This sector is closely related to tourism. The COVID-19 pandemic resulted in a lockdown policy which prevented tourists from visiting Bali. The result is disruption in the tourism sector. Tourism centers such as Kuta and Ubud are like ghost cities because all shops, hotels and restaurants are closed. Even after the restrictions were lifted, tourism sector was still not moving. There are new problems especially in Kuta related to safety and cleanliness. Many shops haven't opened yet because the tourists haven't come yet, while the tourists themselves don't want to come to Kuta because the conditions there don't seem ready. Post-pandemic world economic conditions have also exacerbated the situation, the wars in Russia and Ukraine have disrupted the world economy. Rising inflation and the economy that has not fully recovered have caused people to remain reluctant to travel. The research method used is descriptive qualitative with systematic reviews on papers that raise the issue of unemployment after the COVID-19 pandemic, especially in the tourism sector. The data used is data from BPS and literature with the help of the Google Scholar search engine. This paper contributes to address these issues of unemployment in Bali after the COVID-19 pandemic by conducting literature studies in various locations that have similar problems. This study found that the main challenge in employment in the tourism sector in Bali is the vulnerability to unemployment caused by dependence on foreign tourists and lack of investment. For this reason, the Government has started to carry out stimulus to attract foreign investment while increasing the interest of local tourists to Bali. Starting from building special economic zones, building new industries such as health tourism, and develop infrastructure